2007
DOI: 10.1308/003588407x209400
|View full text |Cite
|
Sign up to set email alerts
|

Financial Implications of Plans to Combat Methicillin-Resistant Staphylococcus aureus (MRSA) in an Orthopaedic Department

Abstract: INTRODUCTION The aim of this study was to calculate retrospectively the cost of MRSA infections in the elective and trauma orthopaedic population in Rotherham District General Hospital in a 3-month period during 2005.PATIENTS AND METHODS A total of 686 patients were admitted to the orthopaedic wards and the surgical wounds 10 patients became infected with MRSA. RESULTS The cost of these infections when extrapolated over 12 months was £384,000 excluding staff costs. CONCLUSIONS The key in the fight against MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Lee et al [34] showed that screening and decolonization was still the most cost-effective choice even when the following parameters were changed to make the protocol less desirable: a second body site was screened, there was a low prevalence of MRSA, and the decolonization success rates were low. Studies in orthopaedic patients [22,36,52] and those having total joint arthroplasty [19,42,43] also showed that implementing a S. aureus screening and decolonization protocol resulted in cost savings, because the cost of treating patients with SSIs with readmission was greater than the costs of instituting the screening and treatment protocol. Hassan et al [22] evaluated the costeffectiveness of instituting PCR as the method of detection for S. aureus colonization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lee et al [34] showed that screening and decolonization was still the most cost-effective choice even when the following parameters were changed to make the protocol less desirable: a second body site was screened, there was a low prevalence of MRSA, and the decolonization success rates were low. Studies in orthopaedic patients [22,36,52] and those having total joint arthroplasty [19,42,43] also showed that implementing a S. aureus screening and decolonization protocol resulted in cost savings, because the cost of treating patients with SSIs with readmission was greater than the costs of instituting the screening and treatment protocol. Hassan et al [22] evaluated the costeffectiveness of instituting PCR as the method of detection for S. aureus colonization.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in orthopaedic patients [22,36,52] and those having total joint arthroplasty [19,42,43] also showed that implementing a S. aureus screening and decolonization protocol resulted in cost savings, because the cost of treating patients with SSIs with readmission was greater than the costs of instituting the screening and treatment protocol. Hassan et al [22] evaluated the costeffectiveness of instituting PCR as the method of detection for S. aureus colonization. Their economic analysis separated the cost of setting up PCR detection for the first year and performing S. aureus screening and decolonization in subsequent years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital-acquired MRSA infections are a drain on the health services by increasing the length of in-patient stay with consequent nursing, medical and therapeutic costs. [14][15][16] The increased morbidity as a result of surgical infection after traumatic injury also incurs a cost to the patient, family and workplace. 17 Orthopaedic patients who acquire infection incur costs which are 2.6 times greater than those of non-infected counterparts.…”
Section: Discussionmentioning
confidence: 99%